Respuesta :

Given:

Midpoint = (2,-14)

One endpoint = (4,-13)

To find:

The another endpoint.

Solution:

Let (a,b) be the another endpoint.

Midpoint formula:

[tex]Midpoint=\left(\dfrac{x_1+x_2}{2},\dfrac{y_1+y_2}{2}\right)[/tex]

Using midpoint formula, we get

[tex](2,-14)=\left(\dfrac{a+4}{2},\dfrac{b+(-13)}{2}\right)[/tex]

[tex](2,-14)=\left(\dfrac{a+4}{2},\dfrac{b-13}{2}\right)[/tex]

On comparing both sides, we get

[tex]2=\dfrac{a+4}{2}[/tex]

[tex]4=a+4[/tex]

[tex]4-4=a[/tex]

[tex]0=a[/tex]

And,

[tex]-14=\dfrac{b-13}{2}[/tex]

[tex]-28=b-13[/tex]

[tex]-28+13=b[/tex]

[tex]-15=b[/tex]

Therefore, the another endpoint is (0,-15).